PENGGUNAAN INTERNET SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Kardina Baondong; Erniati Erniati; Wiwin Mistiani; Hidawati Hidawati; A. Ardiansyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The use of the internet as a learning resource has become an effective alternative for improving the quality of classroom instruction and enhancing students' learning motivation in elementary schools. This study aimed to describe the use of the internet as a learning resource in improving the learning motivation of third-grade students at MIS Al-Khairaat Pombewe. This research employed a qualitative approach using a descriptive research design. Data were collected through observation, interviews, and documentation and were analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The findings revealed that teachers utilized the internet as a learning resource through instructional videos, educational images, and supplementary learning materials relevant to the subject matter, making the learning process more engaging, interactive, and easier for students to understand. The use of the internet positively influenced students' learning motivation, as reflected in increased attention, interest, participation, enthusiasm, and active involvement during classroom activities. Although several challenges were identified, including limited internet connectivity, inadequate learning devices, and limited instructional time, the internet remained an effective learning resource. Therefore, the use of the internet contributes positively to improving students' learning motivation and supports the implementation of more effective and meaningful learning processes in elementary schools. ABSTRAK Pemanfaatan internet sebagai sumber belajar menjadi salah satu alternatif yang dapat meningkatkan kualitas proses pembelajaran sekaligus mendorong motivasi belajar peserta didik di sekolah dasar. Penelitian ini bertujuan untuk mendeskripsikan penggunaan internet sebagai sumber belajar dalam meningkatkan motivasi belajar peserta didik kelas III MIS Al-Khairaat Pombewe. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan dengan uji keabsahan melalui triangulasi. Hasil penelitian menunjukkan bahwa guru memanfaatkan internet sebagai sumber belajar melalui video pembelajaran, gambar edukatif, serta materi tambahan yang sesuai dengan materi pelajaran sehingga proses pembelajaran menjadi lebih menarik, interaktif, dan mudah dipahami peserta didik. Pemanfaatan internet memberikan dampak positif terhadap peningkatan motivasi belajar yang ditunjukkan oleh meningkatnya perhatian, minat, keaktifan, antusiasme, dan partisipasi peserta didik selama mengikuti pembelajaran. Meskipun terdapat beberapa kendala, seperti keterbatasan jaringan internet, perangkat pembelajaran, dan waktu pembelajaran, penggunaan internet tetap mampu mendukung terciptanya pembelajaran yang lebih efektif. Dengan demikian, internet sebagai sumber belajar memberikan kontribusi positif dalam meningkatkan motivasi belajar peserta didik serta mendukung terciptanya proses pembelajaran yang lebih berkualitas di sekolah dasar.